(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
A combination of chemical elements, organic matter and rainfall weaken surface rocks and render them liable to water erosion, but insignificantly affect termite mounds. The study is embarked upon to identify the concentration of Ca, Fe, Na, C, and organic matter content in termite mounds and adjacent soils to deduce the influence of resistance of termite mount to erosion. Data on the chemical elements and organic matter contents were generated through laboratory tests using heat, and an Atomic Absorption Spectrophotometer to read the values. The percentage of the chemical elements was calculated as: Instrument Reading multiplied by Extraction Volume 50ml divided by the weight of samples. The percentage of organic matter contents were determined using weight loss on ignition by an oven-dried soil sample. The set of data was analyzed by comparing the difference in magnitude of the chemical concentration and organic matter content in both the samples. The values differ insignificantly by 0.02%, 0.001%, 0.21%, 0.01%, and 0.24% for Ca, C, Fe, Na, and organic matter respectively. From the result, the resistance of termite mound to erosion is not influenced by the chemical concentration and organic matter content, but due to the maintenance of the mound by the termites, tapering end toward the atmosphere, fairly straight with steep slopes, and have dome shape that reduces effects of forceful fall of the raindrop. Further study should be conducted to determine the influence of chemical elements and organic matter on surface erosion for sustainable development of soils.